A Comparison of Simulation Training and Didactic Teaching Around the Involuntary Detention Process - Adam Flynn; Lorraine Darcy; Linda Clarke; Bronagh Sproule; Chris Sharkey (BJPsych Open)
Aims: Teaching around the involuntary detention process under the Mental Health (Northern Ireland) Order 1986 is typically given to new rotational doctors at changeover. This can include a lot of new and technical information and likely can present as overwhelming. Initially, Quality Improvement Project was commenced to assess whether Forms under the Mental Health Order were being completed correctly pre- and post-traditional changeover teaching session.